KNOWLEDGE MANAGEMENT DAN ASPEK KEWIRAUSAHAAN TERHADAP KINERJA MELALUI KEUNGGULAN BERSAING UKM DI KOTA MAKASSAR - Maharani Maharani; Haris Maupa; Andi Aswan (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
One form of decentralized and diverse populist economic activities is to increase SME development activities. This study aims to analyze how much influence (i) knowledge management and entrepreneurship aspects of SMEs performance; (ii) knowledge management and entrepreneurship aspects of SME performance through competitive advantage; and (iii) competitive advantage over SME performance. This study uses a quantitative approach that emphasizes the analysis of data. This research was conducted in Makassar City, with two months research period. This research data consists of primary data in the form of questionnaires, and secondary data in the form of reports or data of SMEs. The study population is small and medium enterprises in Makassar City. Sampling method is probability random sampling with simple random sampling technique that is random sampling proportionally for each sector of SME sector. Analysis technique used is path analysis to identify direct and indirect influence between variables. The results showed that the variable knowledge management and entrepreneurship aspects significantly influence the performance of SMEs. Knowledge management and entrepreneurship aspects have a significant effect on the performance of SMEs through competitive advantage. Competitive advantage significantly influences SME performance. All hypotheses in this study are accepted.